The Impact of Artificial Intelligence on Women’s Empowerment in Education in Afghanistan - Kefayatullah Khairkhah; Mohammad Nadim Yosouf Zai; Tamanna Quraishi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Artificial Intelligence (AI) has emerged as a transformative tool with the potential to advance education, empowerment, and entrepreneurship for marginalized populations. This study examines the role of AI technologies in enhancing educational access, social empowerment, and entrepreneurial opportunities for Afghan women, who have historically faced sociopolitical and cultural constraints. Using a quantitative descriptive research design, data were collected from 150 students across four faculties at Vision Online University. Findings reveal that the majority of participants are at least somewhat familiar with AI technologies, with 77% perceiving AI as significantly improving learning opportunities for women. AI is recognized not only as a facilitator of personalized education and digital skills acquisition but also as an enabler of financial independence and entrepreneurial engagement. Participants identified key barriers, including limited access to devices and the internet, low digital literacy, and societal restrictions, which impede effective adoption. The study highlights AI’s multidimensional impact in fostering knowledge, autonomy, and economic participation, while emphasizing the need for inclusive implementation strategies. By addressing infrastructural and cultural challenges, AI can serve as a sustainable mechanism for promoting gender equality, social inclusion, and economic development in Afghanistan. These insights underscore the potential of AI to empower Afghan women as active contributors to national progress.